ARIMAX Model to Forecast Grain Production Under Rainfall Instabilities in Brazilian Semi-arid Region (Global Journal of Human-Social Science, 2024)
The state of Cear has most of its area in Brazil s semi-arid region Initially the research segmented Cear s annual rainfall into 6 periods very rainy rainy normal-humid normal-dry drought and very drought This segmentation was based on the annual rainfall in the state between 1901 and 2020 The research estimated the average rainfall and instability of both the annual rainfall in the state during the period and those estimated for the periods in which the rainfall was segmented The research then developed forecast models for harvested areas yields production values and average annual grain prices between 1947 and 2020 the years in which this information is available To make these forecasts the research used the ARIMAX model which is an extension of the Box-Jenkins model with the addition of an exogenous variable The exogenous variable included in the model was the annual rainfall observed between 1947 and 2020 assuming that this variable influences these forecasts The results showed that the state s rainfall has a high level of instability and that the adjusted models proved to be parsimonious and robust from a statistical point of view
Keywords: climate adversity vulnerable ecosystems systematic occurrence of droughts aridity index edaphoclimatic factors